GLOBALIZATION AND HIGHER EDUCATION PROBLEMS IN RUSSIA - A. V. Panibrattsev (Научный вестник МГТУ ГА)
The paper deals with the main challenges of globalization of higher education, a definition of globalization is given. It is noted that globalization was the basis for the transformation of vocational education. The main purpose of the globalization of higher education is to focus on building a society that is based on well-educated human capital. The main directions of globalization are internationalization, integration and computerization of higher education. It is shown that the globalization of education is a concept that orients a student on the development of planetary consciousness.